Group of Twenty : Reinvigorating Trade to Support Growth. (Policy Papers; Policy Paper ;, 2016)
Reinvigorating trade integration should be a key component of the global policy agenda to boost growth. Trade policy's new frontiers such as services, regulatory cooperation, and trade and investment complementarities carry high potential to bolster efficiency and productivity. But with governments differing on whether to continue the WTO Doha Round, there is an urgent need to identify a path for the global trading system in today's more complex trade policy landscape. A long interregnum without a path forward would risk fragmenting the global trade system and undermining its governance. Tackling trade policy issues important to the global economy may require flexible approaches to multilateral negotiations, including modalities such as plurilaterals. Enhanced coherence efforts are also needed to ensure that regional trade agreements and multilateralism coexist productively.